Analysis of Consumer Behavior Towards Purchase Decisions with Online Shopping as A Mediation Variable Fashion Products in Medan City - Soufiana Hayati; Mesra B; Nurafrina Siregar (International Journal of Management, Economic and Accounting, 2024)
The purpose of this study is to test and analyze the influence of social factors, personal factors and psychological factors on the decision to buy online shooping fashion products in Medan City. Testing and analyzing the influence of social factors, personal factors and psychological factors on the purchase decision of fashion products in Medan City through online Shooping. This type of research is quantitative descriptive, with a research sample of 71 customers. Data analysis uses the SEM (structural equality modeling) method. Overall, from the results and discussions in the study, it is concluded that there is a significant influence between social factors on online shopping for the purchase of fashion products in Medan City. There is a positive and significant influence between personal factors on online shopping for the purchase of fashion products in the city of Medan. There is a positive and significant influence between psychology and online shopping for the purchase of fashion products in the city of Medan. There is a positive and significant influence between online shooping on the decision to buy fashion products in the city of Medan. There is a positive and significant influence between social factors on the purchase of fashion products in Medan City through online shooping. There is a positive and significant influence between personal factors on the decision to buy fashion products in Medan City through online shooping. There is a positive and significant influence between psychology and the decision to buy fashion products in Medan City through online shooping.